STRATEGIES FOR DIGITALIZATION OF MANAGEMENT OF UNIVERSITY EDUCATION IN NIGERIA (Journal of Association of Educational Management and Policy Practitioners, 2025)
Digitalization is a powerful engine for economic growth, Digital technologies are being utilized in higher institution of learning but there is a gap that is yet to be filled. Today’s University leaders and Faculties especially in Nigeria must reconsider higher education in a digital-dominated new world, since it is becoming more globalized increasingly important for institution to quickly, efficiently, and appropriately plan the digital information to achieve flexibility. This research reviewed existing literature on the concepts of digitalization as a multi-displinary tool for facilitating learning.